2016
DOI: 10.5194/angeo-34-739-2016
|View full text |Cite
|
Sign up to set email alerts
|

Current sheet flapping in the near-Earth magnetotail: peculiarities of propagation and parallel currents

Abstract: Abstract. We consider series of tilted current sheet crossings, corresponding to flapping waves in the near-Earth magnetotail. We analyse Cluster observations from 2005 to 2009, when spacecraft visited the magnetotail neutral plane near X ∈ [−17, −8], Y ∈ [−16, −2] R E (in the GSM system). Large separation of spacecraft allows us to estimate both local and global properties of flapping current sheets. We find significant variation in flapping wave direction of propagation between the middle tail and flanks. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 58 publications
3
7
0
Order By: Relevance
“…This is consistent with the statistical surveys by Yushkov et al. (2016) and Gao et al. (2018), who found that flapping motions far in the flank propagate toward the sun.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is consistent with the statistical surveys by Yushkov et al. (2016) and Gao et al. (2018), who found that flapping motions far in the flank propagate toward the sun.…”
Section: Discussionsupporting
confidence: 93%
“…Taking advantage of the abundance of the flapping events in the magnetotail, the statistical surveys carried out by Yushkov et al. (2016) and Gao et al. (2018) showed that the wave‐like magnetotail current sheet observed in the flanks propagates away from the midnight sector.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the flapping type described by Sun et al () as propagating toward midnight is probably the steady flapping we found in this study. Yushkov et al () indeed found that the CS normal near midnight tends to be along the Z axis within −6 < Y < 0 R E , and CS is significantly tilted away from the Z axis beyond Y < −6R E (see their Figure 2), but they interpreted it as a significant variation of the direction of flapping wave propagation. In other words, our study not only supports previous findings on the distribution of the CS normal on the Y coordinates but also further enhances knowledge of flapping dynamics in terms of the distribution of flapping types.…”
Section: Conclusion and Discussionmentioning
confidence: 97%
“…It has been noticed in previous studies that the source of flapping motion is located around the midnight region, suggesting such possible sources as fast plasma flow or magnetic reconnection (Sergeev et al, , ). Some studies indeed extended the surveyed region to cover midnight in order to explore features of the sources, but they have remained focused on the normal orientation of each encountered CS rather than on the two flapping types we have described here (e.g., Runov et al, ; Sun et al, ; Yushkov et al, ). For example, with the statistical analysis of each encountered CS normal by Cluster, Sun et al () argued that magnetotail CS could have two types of flapping motions, kink‐like flapping motion propagating toward both flanks and kink‐like flapping propagating toward midnight within | Y | < 8R E .…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Such a shift implies sunward propagation of plasma structures from ThE to ThD (separated mainly in X by ~1.3 R E ) with a velocity of ~40 km/s, which is consistent with the measured average proton bulk flow. A plausible interpretation of this fluctuating By appearance is that the azimuthal CS signatures are modulated by localized sunward convected structures, possibly either the remnants of BBFs produced by time‐varying reconnection, or the flapping wave (flapping waves were also observed in the dawnside plasma sheet; Yushkov et al, ). We recall that these observations were made in the region of return convection near the dawn terminator at 10 to 12 R E .…”
Section: Event Descriptionmentioning
confidence: 99%